Factors that contribute to green neighbourhood: a review - Salleh, Nurul Akma; Zainol, Rosilawati; Ahmad, Faizah; Hj. Mohd. Noor, Norzailawati (Universiti Malaya, 2014)

(untitled)
Human activities such as deforestation, urbanisation and industrialisation have contributed to the increasing amount of carbon dioxide (CO2) deposited in the atmosphere which has become a major issue in this century. CO2 gives a huge impact on greenhouse gasses that lead to climate change, global warming and other environmental disaster. These impacts are very severe, and need to be properly examined in designing a city. A city should move towards a comprehensive green and sustainable development. For the past 10 years, various studies emphasising on green neighbourhood have been published in urban planning research. This paper presents a review of literature prior to 2014 and its current issues based on factors that contribute to green neighbourhood. The review highlighted that green infrastructure, walkability and connectivity, mixed use development and safe neighbourhood as the most prominent factors in a green neighbourhood planning concept. It is also found that these factors contribute towards a more liveable city.